Αγγλικά - Allan's big scary teeth - Δ'-ΣΤ' Δημοτικού Επ. 73 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική IGit Hello, children, and how are you today? I am back again. I teach English and I love stories and I use my stories in my teaching and I've got another story for you today. The story today is about alligators and crocodiles but before I tell you my story I want to see that you know some facts. So, as you know my story is going to take you to places and you're going to meet animals. The first place you're going to go of course is in the jungle. You're going to go into the jungle and can you please tell me what can you find in the jungle? Yes, of course. Trees and more trees and more trees and high trees and what else? Oh yes, of course. Plants, of course. Many plants. Plants. And what else do you find in the forest, in the jungle? You find wild birds and you find wild animals and you find rivers and lakes and swamps. Oh yes, this is another fact I want you to know about a swamp. A swamp is something like a pond. I mean it's a little lake but the water in the swamp does not run, does not move so it's not a clean place and you never swim in a swamp. You swim in the sea. Ok, another thing, another fact I need you to know for my story today is about crocodiles and alligators. Ok, crocodiles, first of all, look at that crocodile. I mean my God, these teeth. Do you see those teeth? Sharp. Sharp like knives. And how many, how many, how many? I didn't know so I read and I read that crocodiles have got 64 teeth. 64 teeth. How many teeth do you have? I mean children are here, here. Children have got like one, two, come with me, two, three, yes, five, eight, nine, ten, right, ten. Ten teeth in the upper jaw and ten teeth in the lower jaw. So you have twenty teeth. Your mum and dad, I mean all grown ups, they have 32 teeth. Yes, sixteen in the upper jaw and sixteen down. So crocodiles have got double the number, twice as many and very sharp. Another fact I want you to know is about the scales that crocodiles and alligators have. I mean their skin, their skin has got scales. What is scales? I mean your body and my body has got skin and human skin is soft but the skin of a crocodile is hard. Now can you tell me what other animals have scales? Yes? What? You can see. An alligator of course, an alligator, an alligator and of course snakes, yes they have scales and fish have scales. What else? A lizard. This is called armadillo lizard, a very strange animal. I have never seen one in real life. And iguanas, yes they have scales and ok, I think now we learned about scales. The other thing I need us to talk about is the differences. Are alligators the same as crocodiles? Well, not exactly. They are like cousins. There are some similarities. What is the same? The same is that they both have very short feet. And the other similarity is that they have, yes of course, scales. And of course, what other similarities there? Oh yes, they live in water. But the crocodiles want salty water. The alligators don't really need that. Now let's go to the differences. An alligator is smaller usually than a crocodile. An alligator can move more quickly than a crocodile. And there is another big difference. Look at their snout. Snout is let's say the mouth of the crocodile. Now with the crocodile the snout is like a V. It's like a V. It's like this, like a V. But with the alligator it's like a U. So what does that mean? When the alligators close their mouths, they hide their teeth. But the crocodiles, they cannot hide their teeth. You can always see the teeth. Oh, I forgot another difference. There is another difference. The alligator is friendlier. But the crocodile is usually in a bad mood. It attacks more easily. So I think I've told you all the facts you need to know. Are you ready for the story? You've got to say, you have to say yes, yes, yes. Yes, yes, yes. Yes, ok, I can hear you. Ok, ok, we're starting. So, once upon a time there was Alan. Alan the alligator. And Alan the alligator lived in a swamp. He lived all on his own and he enjoyed his life. He lived in that jungle and everybody knew him in the jungle. All the birds knew him and all the birds were scared of him and Alan liked it. He liked scaring the animals and he liked the fact that everybody knew him in the jungle. And how did he scare? Well, he opened his big mouth and then he made some twists and turns and he made noises and all the animals were frightened. Alan had a routine. Every day he would get up in the morning and the first thing he would do, he would clean his scales. Because we said that he has scales, ok. The next thing he would do, he would sharpen his nails, his clothes. Like we all have nails. Some people have longer nails, others have shorter nails. Well, Alan the alligator would sharpen his nails. The third thing he would do, he would brush his teeth for ten whole minutes. He was very careful with his teeth. And then he would get in front of his mirror because he found that mirror and he liked it. And now he looked in the mirror and he practiced making scary faces and because he practiced that's why he was so good. And once he was ready, he would start his routine and he would go into the jungle. And what would happen? Everybody would be scared. The frogs would start leaping from lily pad to lily pad. And the monkey, they would jump from branch to branch, very frightened. And the parrots, they would screech and jump from one branch to the other to get away. And of course Alan would enjoy every minute of it. And when the day passed he would go back to his swamp and he would play a bit, he would eat a bit and then he would rest. He would sleep. But to sleep he would have to take off his teeth. Oh yes! Alan had false teeth and he loved his teeth very much and he took very good care of them. So that night he put them in the super hiding place in a bush, in a little tree and then he lay down to sleep. He lay down to sleep and in the morning, early in the morning, we had beaver, beaver, beaver, beaver. Barry the beaver was moving around because he was looking for nuts, because you know they look nuts. And he was hopping, hopping, hopping, trying to find nuts and then he came across, he saw Alan and froze. And then he went backwards and backwards because what if Alan sees him, he would eat him up. And he moved back and he moved back and in the bush he just waited a bit because he wanted to get calm and there he saw the teeth. Teeth? Really? Are these Alan's teeth? Is that a joke? No, it isn't. They are false and he gets them and he holds them and runs away and disappears. And the next day Alan wakes up. Alan wakes up and the first thing he will do, he will go and find his teeth in the super hiding place. But the teeth were nowhere. He looked here, he looked there, he looked everywhere. He didn't know what to do. What happened here? And how could he go to the forest now? And how could he scare? He was scared himself. He didn't know that morning, he didn't do his routine. But around, like after a few hours, he decided to go and now he would pretend, he would pretend that he still had his teeth. So slowly and with his head down he went to the jungle and the frogs saw him and the frogs leaped and leaped but they were not frightened, they were laughing. And further down the monkeys, oh the monkeys looked at Alan, they looked at Alan and they were not frightened, they were laughing. And the parrots, and the parrots, they were very curious and they were looking at Alan and they were not scared, they were laughing. And Alan knew that everybody knew his secret and with his head down he decided to go back to his swamp, to go back to his place. And there he sat and he didn't know, he started crying and he started crying like a baby, like all the babies in the jungle could not make that big noise. And the rest, you see, the crocodile tears, they were real and they were coming and that night he could not sleep. And the next day he was not in the mood, he wanted to die, there was no purpose in his life, the only thing he knew in his life was to scare, what would he do now? And then slowly around him came the frogs and they sat at a distance without moving, without saying anything and then the monkeys came around and they also sat down. And then the parrots came and they just stood, they didn't do anything and Alan was looking at them, he didn't know what to say. And then finally, and then finally Beaver came and Beaver came and Beaver was holding his false teeth. Oh Alan found his teeth, can you please give me my teeth, they are mine. Not so fast, not so fast, said all the animals, but why? These are my teeth, please, please. And after some time the animals said, on one condition, on one condition, said Beaver. What condition, what condition? You will promise that you will not frighten us anymore, but that's the only thing I know to do, what am I going to do? You've got to promise and the monkey said that every day he can learn something new, that in our lives we learn new things and then he realized that he had to promise. And Beaver gave Alan his false teeth and Alan put them on, he put them on and he said, yes, I will not scare you, but what can I do? And the monkey said, you can be the gardener and the beaver said, yes, you can be the gardener, you can collect nuts, you can collect fruit, you can collect food for us. And that's what, from that day, that's what Alan did. Every morning he would go in the jungle and he would collect nuts and he would collect berries and he would collect other fruit for the animals and in the afternoon the animals would meet, they would eat and Alan would tell them scary tales. He became a storyteller as well and sometimes he gave his false teeth to Barry to play with. And we're coming to the end of the story, but you know the question is, what do we understand from this story? What can you tell me? What is really the meaning of this story? Really? You found it. Yeah, it's about bullying because yes, Alan was a bully. I mean, he used his power and strength to make the other animals suffer. But you know what, when you're strong, you don't use your strength to make others suffer, you use your strength for a good purpose. Like at the end of the story where Alan collected food with all his strength and helped the whole community. And so I think that is the message with Alan, with his scary false teeth and that's the end of our story for today. See you again. Bye bye.